Assessing the Impact of Talent Management Practices on Employee Retention in Aligarh's IT Industry - Singh, Megha; Bhardwaj, Sanjeev (Integrated Journal for Research in Arts and Humanities, 2024)
Talent management has become increasingly critical for organizations to attract and retain high-performing employees, especially in competitive industries such as information technology (IT). This study aims to assess the impact of talent management practices on employee retention in the IT industry in Aligarh, India. A quantitative research approach was employed, with data collected through a survey of 342 IT professionals working in Aligarh. Factor analysis and multiple regression were used to analyze the data. The findings reveal that talent management practices such as employee development, career management, compensation and rewards, and work-life balance have a significant positive impact on employee retention. Performance management was not found to have a significant relationship with retention. The results suggest that IT companies in Aligarh should focus on implementing effective talent management strategies to improve employee retention and gain a competitive advantage. This research contributes to the literature by providing empirical evidence on the role of talent management in retaining employees in the IT domain in an Indian context.